The Strategic Role of Midwives in the Implementation of Family Planning Programs: Increasing Public Awareness and Participation in Reproductive Health - Oktafiana Manurung; Dini Marlina; Avid Leonardo Sari; Abdul Rasyid Saliman; Karningsih Karningsih (Universitas Aisyah Pringsewu, 2023)
The Family Planning Program (KB) is the government's mainstay in suppressing the population growth rate. Increasing public awareness and participation in maintaining reproductive health is one of the efforts to make the family planning program successful. For this reason, the active Role of several parties is needed in providing education about reproductive health. Midwife. Midwives, as health workers, are considered to be essential subjects in carrying out this education because midwives provide counselling or communication, information and education (IEC) to the public about the importance of maintaining reproductive health. Therefore this study aims to analyze the strategic Role of midwives in implementing family planning programs, especially in increasing public awareness and participation in reproductive health. This study uses a qualitative descriptive research method. The results of the study showed that Permenkes 1464/Menkes/Per/X/2010 gave authority to midwives to provide services and counselling on reproductive health to the community so that midwives have a strategic role in increasing public awareness and participation in maintaining their reproductive health. The midwife's Role, in this case, can be seen as a manager, educator, facilitator and motivator. However, midwives are often faced with various challenges in carrying out their roles, such as limited resources, lack of government support, socio-cultural problems in the community and lack of public knowledge.